Star-forming, rotating spheroidal galaxies in the GAMA and SAMI surveys. Issue 2 (12th August 2019) - Moffett, Amanda J; Phillipps, Steven; Robotham, Aaron S G; Driver, Simon P; Bremer, Malcolm N; Cortese, Luca; Wong, O Ivy; Brough, Sarah; Brown, Michael J I; Bryant, Julia J; Conselice, Christopher J; Croom, Scott M; et al.
ABSTRACT: The Galaxy And Mass Assembly (GAMA) survey has morphologically identified a class of 'Little Blue Spheroid' (LBS) galaxies whose relationship to other classes of galaxies we now examine in detail. Considering a sample of 868 LBSs, we find that such galaxies display similar but not identical colours, specific star formation rates, stellar population ages, mass-to-light ratios, and metallicities to Sd-Irr galaxies. We also find that LBSs typically occupy environments of even lower density than those of Sd-Irr galaxies, where ∼65 per cent of LBS galaxies live in isolation. Using deep, high-resolution imaging from VST KiDS and the new Bayesian, 2D galaxy profile modelling code profit, we further examine the detailed structure of LBSs and find that their Sérsic indices, sizes, and axial ratios are compatible with those of low-mass elliptical galaxies. We then examine SAMI Galaxy survey integral field emission line kinematics for a subset of 62 LBSs and find that the majority (42) of these galaxies display ordered rotation with the remainder displaying disturbed/non-ordered dynamics. Finally, we consider potential evolutionary scenarios for a population with this unusual combination of properties, concluding that LBSs are likely formed by a mixture of merger and accretion processes still recently active in low-redshift dwarf populations. We also infer that if LBS-like galaxies were subjected to quenching in a rich environment, they would plausibly resemble cluster dwarf ellipticals.